Effects of state-level Earned Income Tax Credit laws in the U.S. on maternal health behaviors and infant health outcomes. (December 2017) - Markowitz, Sara; Komro, Kelli A.; Livingston, Melvin D.; Lenhart, Otto; Wagenaar, Alexander C.
Abstract: The purpose of this paper is to investigate the effects of state-level Earned Income Tax Credit (EITC) laws in the U.S. on maternal health behaviors and infant health outcomes. Using multi-state, multi-year difference-in-differences analyses, we estimated effects of state EITC generosity on maternal health behaviors, birth weight and gestation weeks. We find little difference in maternal health behaviors associated with state-level EITC. In contrast, results for key infant health outcomes of birth weight and gestation weeks show small improvements in states with EITCs, with larger effects seen among states with more generous EITCs. Our results provide evidence for important health benefits of state-level EITC policies. Highlights: State-level EITC generosity is associated with improved birth outcomes. States with refundable EITCs had the largest increases in birth weights and reductions in prevalence of low-weight births. Gestation increases slightly along with state EITC generosity. EITC policies do not appear to affect the hypothesized mechanisms of early prenatal care and reduced smoking.